Computer Science &Amp; Information Technology (CS &Amp; IT) 2012
DOI: 10.5121/csit.2012.2360
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Digital Watermarking Technique for Video Copyright Protection

Abstract: Abstract:Due to the rapid growth of internet and technology, protecting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The proposed system demonstrated that the procedure is extremely reliable. Poulami Ghosh et al [27] presented a new watermarking approach in 2012 that included both visible and invisible watermarks in a video. Because digital data may be easily duplicated without deterioration in quality, data protection is required.…”
Section: Frequency Domainmentioning
confidence: 99%
“…The proposed system demonstrated that the procedure is extremely reliable. Poulami Ghosh et al [27] presented a new watermarking approach in 2012 that included both visible and invisible watermarks in a video. Because digital data may be easily duplicated without deterioration in quality, data protection is required.…”
Section: Frequency Domainmentioning
confidence: 99%
“…There are number of researchers has focused on watermarking in video using edge and corner regions, the most recent researches are explained as follow: Ghosh et al [9] proposed a novel Watermarking technique whether visible and invisible watermarks are embedded in the video by using Discrete Wavelet transform (DWT) which gives an extraction edge in the copyright protection. The suggested algorithm works properly on gray scale and on video of uncompressed (AVI format) that protected a video from illegal access by embedding watermarks into video, Peak Signal to Noise Ratio (PSNR) is calculated to measure efficiency of this method.…”
Section: Related Reviewmentioning
confidence: 99%
“…Through DWT signals can be analyzed at different level called as multi resolution analysis [6]. Unlike DCT, in DWT transformation is applied on whole image, not on nonoverlapped 2-D blocks.…”
Section: Discrete Wavelet Transformationmentioning
confidence: 99%